Relation Between Reading Performance and White-Matter Alteration and Reorganization in Neurosurgical Patients - Cargnelutti, Elisa; Maieron, Marta; Ius, Tamara; Skrap, Miran; Tomasino, Barbara (Frontiers in Neurology, 2020)
Reading abilities and diffusion tensor imaging (DTI) parameters were retrospectively analyzed in a group of neurosurgical patients to investigate (Study 1) the role of white matter – in particular the arcuate fasciculus (AF) – in preserved vs. impaired reading; four months after surgery, we explored plasticity processes (Study 2). Study 1 involved 40 patients with brain glioma (23 low-grade and 17 high-grade gliomas). We compared preoperative DTI parameters of language-related fascicles between patients who developed a reading impairment after surgery (n = 23) and patients with preserved reading (n = 17). Besides lower fractional anisotropy (FA), patients with impaired reading also displayed lower number and density of streamlines of a direct (i.e., directly connecting temporal and frontal lobes) AF segment. In Study 2, we longitudinally tested at follow-up 13 patients diagnosed with low-grade glioma, when reading performance had generally improved. The most relevant finding was a significant increase in length of streamlines of the direct AF segments in both hemispheres. From a neurosurgical perspective, our preliminary findings suggest the clinical importance of sparing direct AF segments for the involvement they showed in reading; however, the results also suggest the reorganization potential of these segments, possibly compensating of the right homologues as well.